Seamless Communication for Crisis Management - Wojciechowicz, Wojciech; Fournier, Jacques; Konecny, Miroslav; Vanya, Stefan; Stoodley, John; Entwisle, Phil; Hein, Daniel M.; Machalek, Aurel; Fournaris, Apostolos; Uriarte, Mikel; Lopez, Oscar; O’Neill, Shaun; et al. (My University, 2012)
SECRICOM – Seamless Communication for crisis management was a research and development project, realised within the Seventh Framework Programme (7PR). The aim of this project was to develop reference solution based on existing infrastructure, which will be capable to ensure secure and efficient communication for operational crisis management. The project was an answer to the European Security Research Advisory Board (ESRAB) report, in which key requirements for a communication system have been stated. Secure and efficient communication system is a necessity for effective crisis management. It is assumed that such infrastructure may significantly increase rescue actions effectiveness. Currently, however, there are cases when various services (not only domestically but also internationally) use heterogeneous telecommunications systems. It results in the lack of or significant problems with mutual communication. Such situation is often considered problematic and posing a threat to the effective rescue actions. For this purpose, a secure and multi-platform communications system (SECRICOM Silentel) has been developed within SECRICOM project. The Multi Bearer Router (MBR) optimise the backbone network by the use of multiple bearers and dynamic adjustment to various conditions. Advance mechanisms enhancing end-user devices’ security – Secure Docking Module (SDM) – have been developed using Trusting Computing principles. Secure Agent Infrastructure (SAI) ensures – based on agents’ infrastructure – secure access to distributed data. The system is supplemented with network monitoring platform – Communication Security Monitoring and Control Centre. The SECRICOM project resulted in a communication system prototype, which is capable of ensuring interoperability as well as secure and efficient communication for operational crisis management. This system has been demonstrated on several occasions to the stakeholders.

SECRICOM – Seamless Communication for crisis management to projekt badawczo-rozwojowy, który został zrealizowany w ramach siódmego programu ramowego (7PR). Celem projektu było wypracowanie bezpiecznej i, co ważne, bazującej na istniejącej infrastrukturze platformy komunikacyjnej do operacyjnego zarządzania kryzysowego. Projekt ten stanowi odpowiedź na raport European Security Research Advisory Board (ESRAB), w którym określono najważniejsze wymagania odnośnie do systemu komunikacji. Bezpieczny i wydajny system komunikacji jest warunkiem koniecznym do efektywnego zarządzania w sytuacjach kryzysowych. Przyjmuje się, że taka platforma jest w stanie znacząco zwiększyć efektywność prac służb ratunkowych. Obecnie jednak są przypadki, gdy służby ratunkowe (nie tylko na arenie międzynarodowej, lecz także podczas działań w jednym kraju) korzystają z niejednorodnych systemów telekomunikacyjnych, co często skutkuje brakiem lub istotnymi problemami z wzajemną łącznością. Sytuacja ta jest postrzegana jako problematyczna i stanowi zagrożenie dla efektywnego działania służb ratunkowych. W ramach projektu SECRICOM opracowano system międzyplatformowej, bezpiecznej łączności SECRICOM Silentel. Za optymalizację transmisji danych (w tym wykorzystanie wielu nośnych oraz dynamiczne dostosowywanie się do warunków) w sieci dystrybucyjnej oraz szkieletowej odpowiada Multi Bearer Router (MBR). Zaawansowane mechanizmy zwiększające bezpieczeństwo urządzeń końcowych – Secure Docking Module (SDM) – opracowano z wykorzystaniem pryncypiów Trusted Computing. Secure Agent Infrastructure (SAI) zapewnia – oparty na infrastrukturze agentów – bezpieczny dostęp do rozproszonych danych. System uzupełnia platforma nadzoru nad siecią – Communication Security Monitoring and Control Centre. Jako rezultat projektu zbudowano oraz kilkukrotnie zademonstrowano prototypową wersję systemu komunikacji. System ten jest zdolny do zapewnienia interoperacyjnej, bezpiecznej i wydajnej łączności w zarządzaniu w sytuacjach kryzysowych.
Keywords: SECRICOM; Seamless communication; crisis management; Multi Bearer Router (MBR); Push To Talk (PTT); SECRICOM Silentel; Secure Docking Module (SDM); Secure Agent Infrastructure (SAI); Communication Security Monitoring and Control Centre (CSMCC); Seventh Framework Programme (FP7); Trusted Computing; „bezszwowa” komunikacja; zarządzanie kryzysowe; siódmy program ramowy (7PR)